The Relationship between Public Debt, Budget Deficit, and Sustainable Economic Development in Developing Countries: The Role of Corruption Control - Vo Thi Thuy Van (Universitas Muhammadiyah Yogyakarta, 2020)
This study investigates the effects of public debt and budget deficits on the sustainable economic development of developing countries, taking into account the role of control of corruption. The two-step GMM method was applied for unbalanced panel data of 59 developing countries from 2004 to 2015. The study found that public debt and the budget deficit had negative effects on sustainable development, while the effect of control of corruption was positive. Moreover, using interaction terms between control of corruption and public debt and budget deficit, respectively, empirical results showed that controlling corruption limited these adverse effects. Thus, if the objective is to achieve sustainable economic development, developing countries should not see raising public debt or maintaining budget deficits as a strategy for economic development. The study contributes empirical evidence to the theory of debt overhang, crowded effects, and institutional theory in the context of developing countries. The implications are also discussed in this paper.